Detecting life traces in extreme cold and dry conditions on earth: possible analogues of life on Mars - Wierzchos, Jacek; Ríos, Asunción de los; Ascaso, Carmen (European Space Agency, 2004)
3 páginas, 4 figuras Microbial life in the hars conditions of Antarctica's cold desert may be considered an analogue of potential life on early Mars. The microbial ecology of these lithobiontic, extremophile microorganism communities could provide clues to the challenging question of how life (if ever oresent) became extinct on Mars. Application of the SEM-BSE plus EDS technique has allowed us to demonstrate the presence of microbial fossils and biomarkers within Antarctic sandstone rocks collected from Ross Desert for the first time. There is an obvious need for extensive further work on live, dead, mummified and mineralized lithobiontic Antarctic microorganisms. The in situ examination of the interior of Antarctic rocks might represent the best option available to improve our knowledge on these extreme cold and dry microbial habitats and it is foreseen that this type of work will have applications in future astrobiological investigations performed on geological material obtained from Mars. Thanks are due to Prof. E.I. Friedmann for supplying the Antarctic sandstone rock samples from Mount Fleming, to A. Burton for the English revision. This study was funded by grant number ANT99-0680-C02-02, REN2002-03542 and REN2003-07366-CO2-O2 of the Plan Nacional I+D, and BOS2000-1121 and BOS2003-02418 from the PGC. Peer reviewed